2017
DOI: 10.1007/s00125-017-4297-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease biomarkers are associated with declining renal function in type 2 diabetes

Abstract: Aims/hypothesisWe investigated whether biochemical cardiovascular risk factors and/or markers of subclinical cardiovascular disease were associated with the development of reduced renal function in people with type 2 diabetes.MethodsA cohort of 1066 Scottish men and women aged 60–74 years with type 2 diabetes from the Edinburgh Type 2 Diabetes Study were followed up for a median of 6.7 years. New-onset reduced renal function was defined as two eGFRs <60 ml−1 min−1 (1.73 m)−2 at least 3 months apart with a > 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
0
17
2
Order By: Relevance
“…An association with eGFR decline was described also for CVD biomarkers, especially high-sensitivity troponin T [140] and left ventricular ejection fraction [141], possibly reflecting the contribution of chronic cardiac dysfunction to progressive eGFR impairment in the context of type 2 cardio-renal syndrome [142]. In addition, arterial stiffness, a marker of arteriosclerosis, was found to be negatively associated with eGFR [143] and to independently predict eGFR decline [141,144], possibly reflecting the contribution of highly pulsatile pressure and flow to small vessel disease in the kidney [145].…”
Section: Biomarkers Of Egfr Decline Beyond Albuminuriamentioning
confidence: 88%
“…An association with eGFR decline was described also for CVD biomarkers, especially high-sensitivity troponin T [140] and left ventricular ejection fraction [141], possibly reflecting the contribution of chronic cardiac dysfunction to progressive eGFR impairment in the context of type 2 cardio-renal syndrome [142]. In addition, arterial stiffness, a marker of arteriosclerosis, was found to be negatively associated with eGFR [143] and to independently predict eGFR decline [141,144], possibly reflecting the contribution of highly pulsatile pressure and flow to small vessel disease in the kidney [145].…”
Section: Biomarkers Of Egfr Decline Beyond Albuminuriamentioning
confidence: 88%
“…In longitudinal population-based studies, increased CIMT has been associated with progression of albuminuria [22], incident CKD [23] and incident ESRD [36]. However, longitudinal studies in patients with type 2 diabetes are scarce and with opposing findings [20, 21]. A previous study, with 162 individuals followed-up for 6 years, reported that CCA-IMT was associated with renal function deterioration [20]; whereas another study, with 1066 individuals followed-up for 6.7 years, reported no association between CCA-IMT and declining renal function [21].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, although several previous cross-sectional analyses reported associations between carotid atherosclerosis and prevalent microvascular complications in individuals with diabetes [1219], longitudinal studies evaluating ultrasonographic carotid parameters as predictors of future development and progression of microvascular complications are scarce, mainly related to renal function deterioration, and with opposing findings [20, 21]. In population-based studies, CIMT has been shown to be associated with albuminuria progression [22] and with incident chronic kidney disease [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the severity of DKD has been reported to be positively correlated with CIMT, and DKD should therefore be considered as another probable independent risk factor that contributes to atherosclerosis development [ 27 ]. However, contradictory results in the current literature suggest that patients with DKD do not have increased CIMT, particularly so in patients with early-stage DKD [ 12 ]. Consistent with these results, no association was found between early-stage DKD and CIMT in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, results contradictory to the observations have also been reported. There have been several epidemiological reports suggesting no associations between DKD and CIMT [ 12 , 13 ]. This is particularly true in the relationship between early-stage DKD and CIMT [ 14 ].…”
Section: Introductionmentioning
confidence: 99%